2020
DOI: 10.1007/978-3-030-52287-2_22
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Inform the Design of a Supportive Environment for Challenge-Based Collaboration

Abstract: In the course "An introduction to FinTech: from mobile payments to blockchains", students are introduced to the broad area of FinTech, from both technical and business side. The course consists of two technical lectures that explain the students the basic technology for authentication and blockchain and two entrepreneurship lectures that discuss the fintech business ecosystem. In the rest of the course the students work on a project provided by companies in which they put into practice the obtained knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
4
0
5
Order By: Relevance
“…Estos elementos son recogidos del estudio piloto realizado por la empresa Apple cuyo objetivo era hacer que la educación superior fuera más motivadora y relevante para los estudiantes (Baloian et al, n.d.;Leijon et al, 2022;Pisoni & Gijlers, 2020). Dicho estudio piloto se enfocó en la educación superior de ingeniería, con una visión hacia el aprendizaje como una experiencia multidisciplinaria colaborativa, en un contexto internacional, con el objetivo de encontrar una solución sostenible.…”
Section: Contextounclassified
“…Estos elementos son recogidos del estudio piloto realizado por la empresa Apple cuyo objetivo era hacer que la educación superior fuera más motivadora y relevante para los estudiantes (Baloian et al, n.d.;Leijon et al, 2022;Pisoni & Gijlers, 2020). Dicho estudio piloto se enfocó en la educación superior de ingeniería, con una visión hacia el aprendizaje como una experiencia multidisciplinaria colaborativa, en un contexto internacional, con el objetivo de encontrar una solución sostenible.…”
Section: Contextounclassified
“…Students' perceptions on groupwork can also be influenced by the behavior of other team members (Chang and Brickman, 2018; Pisoni and Gijlers, 2020). If a student feels that they are making valuable contributions but their team members are not, the student's perceptions of groupwork might be negatively inclined, possibly resulting in negative group experiences and low group performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is because social cues are more difficult to be transmitted and interpreted online (Korkmaz and Yesil, 2011;Simon and Stauber, 2011). Lacking social presence might result in an imbalance commitment (Pisoni and Gijlers, 2020). The mentioned challenges might also affect the effectiveness of collaborative learning and students' motivation (Korkmaz and Yesil, 2011;Mayer, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important in any group work students to maintain a work environment where people with different skills can perform together in harmony, communicate openly with one another, improve upon each other's ideas, prevent problems before they occur, and learn the right lessons from past projects. New online education approaches have been deployed recently to promote the development of abilities to work in teams for students, and previous research has shown that teaching innovation and entrepreneurship is rather important for this aim [7]. Another scholars employed computational approach to study the dynamics of virtual student teams by examining their Trello activity [8].…”
Section: Introductionmentioning
confidence: 99%